Human Resource Management in Muhammadiyah Junior High Schools in Padang City - Maigus, Maigus (Ruhama : Islamic Education Journal, 2025)
Globally, educational institutions face the challenge of transitioning from administrative Human Resource Management (HRM) to Strategic HRM (SHRM) to enhance quality and competitiveness. This challenge is acute for value-based institutions like Islamic schools, which must align HR practices with both academic goals and religious mission. This study aims to analyze the implementation and strategic alignment of HRM in Muhammadiyah Junior High Schools in Padang City, Indonesia. Employing a mixed-methods sequential explanatory design, data were collected through surveys of teachers and staff, followed by interviews, focus group discussions, and document analysis with principals and officials. The findings reveal significant strategic misalignment. HR planning is reactive, recruitment lacks a value-based competency framework, training overlooks pedagogical methods for integrating Islamic values, performance appraisal is overly administrative, and compensation fails to leverage non-financial religious motivators. This results in a dual misalignment: a vertical disconnect from the school's Islamic mission and a horizontal incoherence among HR functions themselves. The study concludes that a transformative shift towards a comprehensive, value-based SHRM model is essential for these schools to effectively produce graduates who are both intellectually competent and spiritually grounded.